Analisis Pengelolaan Manajemen Sumber Daya Manusia Dalam Upaya Meningkatkan Kinerja Dan Motivasi Melalui Reward System - Ricia Ratri Widodo; Agus Wahyudi; Dewi Cantika Rahmawati; Linda Ratna Fitria Cahyani; Nila Masluha Sukma Nahdliyana (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Human resources (HR) play a crucial role in the functioning of organizations and companies, as their operations are fundamentally dependent on effective human resource management. Regardless of their structure or objectives, organizations are established with a vision and mission aimed at fulfilling human needs, and they are operated by individuals. The management of human resources is essential for organizational success. This article provides a concise analysis of managerial strategies that can be employed through the Reward System to enhance performance and boost motivation, ultimately contributing to the success of the organization or company.